The role of the muscarinic system in regulating estradiol secretion varies during the estrous cycle: the hemiovariectomized rat model - Rodríguez Jorge O; Meléndez Griselda; Palafox María T; Flores Angélica; Cruz María E; Chavira Roberto; Domínguez Roberto (BMC, 2006)
Abstract There is evidence that one gonad has functional predominance. The present study analyzed the acute effects of unilateral ovariectomy (ULO) and blocking the cholinergic system, by injecting atropine sulfate (ATR), on estradiol (E2) serum concentrations during the estrous cycle. The results indicate that ULO effects on E2 concentrations are asymmetric, vary during the estrous cycle, and partially depend on the cholinergic innervation. Perforation of the left peritoneum resulted in lower E2 serum concentrations in the three stages of the estrous cycle. At proestrus, unilateral or bilateral perforation of the peritoneum resulted in lower E2 serum concentrations. ULO of the right ovary (left ovary in situ) resulted in significantly higher E2 concentrations than animals with ULO of the left ovary (right ovary in situ). ATR treatment to ULO rats on D1 resulted in a significant drop of E2 serum concentrations. ULO rats treated with ATR on D2 or P, resulted in an asymmetrical E2 secretion response; when the right ovary remained in situ an increase in E2 was observed, and a decrease when the left ovary remained in situ. The results obtained in the present study suggest that each ovary's ability to compensate the secretion of E2 from the missing ovary is different and varies during the estrous cycle. The results also suggest that the cholinergic system participates in regulating ovarian E2 secretion. Such participation varies according to the ovary remaining in situ and the stage of the estrous cycle of the animal. The results agree with previously stated hypothesis of a neural pathway arising from the peritoneum that participates in regulating E2 secretion, and also supports the idea of cross-talk between the ovaries, via a neural communication, that modulates E2 secretion.